Effect of zirconia stabilized by ittria additions on the structure and mechanical properties of alumina based ceramics - Warcholinski, B.; Gilewicz, A.; Lupicka, O.; Rochowicz, J.; Sayenko, S.; Svitlychnyi, Y.; Zykova, A. (Functional Materials, 2014)
The ceramic samples of pure alumina and alumina with additions of 10, 15, 20 wt. % ZrO₂ stabilized by 5.3 % wt. Y₂O₃ were produced by slip casting method with the subsequent sintering. The enhancement of ceramic mechanical parameters such as Vickers hardness, bending strength, fracture toughness, thermal resistance, wear resistance due to additions of ZrO₂ (5.3 % Y₂O₃) was observed. The effect of additions of ZrO₂ on the formation of dense, tough and fine-grained structure of alumina ceramics was determined. The best complex of mechanical parameters was obtained on the alumina samples with 15 wt. % ZrO₂